Nutritional characterization of yogurts available on the Portuguese market in 2020. Sugar compliance with Portuguese EIPAS - Lopes, Andreia (2022)
Objectives: To evaluate yoghurts nutritional composition and in particular sugar content in both solid and liquid yoghurts available on the Portuguese market and confront obtained values with the targets set by EIPAS of 5 g/100 g; to support policy makers.